A combined diffusion tensor imaging and magnetic resonance spectroscopy study of patients with schizophrenia - Reid, Meredith A. (Schizophr Res, 2015)
Diffusion tensor imaging (DTI) studies in schizophrenia consistently show global reductions in fractional anisotropy (FA), a putative marker of white matter integrity. The cingulum bundle, which facilitates communication between the anterior cingulate cortex (ACC) and hippocampus, is frequently implicated in schizophrenia. Magnetic resonance spectroscopy (MRS) studies report metabolic abnormalities in the ACC and hippocampus of patients. Combining DTI and MRS offers exploration of the relationship between cortical neuronal biochemistry and the integrity of white matter tracts connecting specific cortical regions; however, few studies have attempted this in schizophrenia. Twenty-nine schizophrenia patients and twenty controls participated in this 3T imaging study in which we used DTI and tract-based spatial statistics (TBSS) to assess white matter integrity and MRS to quantify metabolites in the ACC and hippocampus. We found FA reductions with overlapping radial diffusivity (RD) elevations in patients in multiple tracts, suggesting white matter abnormalities in schizophrenia are driven by loss of myelin integrity. In controls, we found significant negative correlations between hippocampal N-acetylaspartate/creatine and RD and axial diffusivity (AD) as well as a significant negative correlation between FA and ACC glutamate+glutamine/creatine in the hippocampal part of the cingulum bundle. It is possible that the extent of myelin damage could have resulted in the absence of DTI–MRS correlations in our patient group. In conclusion, we demonstrate the potential utility of a multi-modal neuroimaging approach to help further our understanding of the relationship between white matter microstructure and neurochemistry in distinct cortical regions connected by white matter tracts.